Application rates to surgical residency programs in Canada - Todd Dow (Canadian Medical Education Journal, 2019)
Purpose: The purpose of this study is to identify if the previously reported declining interest in surgery amongst medical students persists, and also to provide more descriptive analysis of trends by surgical specialty and medical school. Our hypothesis is that the previously reported decreasing interest in surgery remains constant for some surgical disciplines.